Investigation of cell responses on a novel biomaterial membrane - Wee, Teck Shiun. (2011)
Conventional poly(ε-caprolactone) (PCL) membrane fabrication techniques such as solvent casting raises concerns pertaining to toxicological methodology. A novel PCL membrane fabrication method, surface tension melt (STM) technique has been developed for tissue engineering applications, in particular as a potential dermal replacement. The preparations and surface characterization of STM fabricated PCL membranes are documented in this report. Simple surface modification techniques were administered on the PCL membranes, where the PCL membranes were pretreated using acetic acid, sodium hydroxide, collagen and collagen (centrifuged). The modified PCL membrane surfaces were characterized using scanning electron microscopy (SEM), light confocal imaging profiler and wettability of the surfaces were evaluated using the sessile drop method. Results documented showed that wettability of the surface has improved after surface modification, with a drop in water contact angles from 80 o to 63 o. The confocal imaging profiling of the surfaces showed an increase in the surface roughness of the PCL membranes from 4.309 μm to 4.912 μm, 5.139 μm, and 6.023μm. Visual transformations of surface morphologies were also observed from the scanning electron micrographs. The ideal substrate surface that will support and promote cellular proliferation has always been a persistent field of interest in tissue engineering. Besides biocompatibility of the material substrate, issue of cell proliferation is also imperative. This report documented in-vitro cellular viability assessments of Human Dermal Fibroblast (HDF) on the modified PCL membrane surfaces. The proliferative activity of cultured cells on the PCL specimens was determined with MTT colorimetric assay over 3 days and 7 days incubation period. HDF were found to attach and proliferate on all the surface modified PCL membrane with a slight decline in proliferative level in one sample type after 3 days of incubation. Higher HDF proliferation level was observed on the different surface modified PCL samples on the 7th day of incubation. Results revealed that collagen (centrifuged), being closer to HDF native environment displayed higher proliferative level over other surface modification sample types. Overall the results revealed that STM fabricated PCL membrane are favourable material substrates for the growth of HDF, higher HDF proliferation levels were observed on all the surface modified PCL membrane sample types. This project’s evaluation demonstrates the feasibility of STM fabricated PCL membrane as an alternative utility for skin repair or as a potential dermal equivalent or skin graft.